Iron deficiency screening with content hemoglobin reticulocyte (chr) in children aged 6 months to 5 years - Dea Noviana Pramantik; Tri Ratnaningsih; Budi Mulyono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
Anemia is a major health problem around the world and iron deficiency is the major cause. In children under 5 years old iron deficiency cause disruption in their growth and development. For that reasons iron deficiency in children should be detected as early as possible. The gold standard for the detection of iron deficiency is hemosiderin examination from bone marrow aspiration, but this examination is invasive and difficult to implement. Ferritin is often used to detect iron deficiency but it has various limitations. Reticulocyte hemoglobin content (CHr) was introduced as a new parameter for the identification of iron deficiency. This parameter measures the levels of hemoglobin in the reticulocyteswhich is newly released from bone marrow and expected to reflect the actualconditions in the bone marrow, therefore it can detect early iron deficiency. It is expected that CHr can identify iron deficiency with cheaper, easy, and applicative method. The aim of this study was to determine the diagnostic performance of CHr in screening of iron deficiency in children aged 6 months to 5 years old. The present study was a cross sectional study to determine the diagnostic performance of CHr and use ferritin as gold standard. The subjects of this study were healthy children aged 6 months-5 years old taken from Posyandu in Yogyakarta district and previously had obtained the consent of their parent/guardian. The CHr examination used a flowcytometry method by Advia120 Hematology Analyzer. The ferritin examination used an electrochemiluminescens method with Elecsys 1010. ROC curve analysis was performed using SPSS version 17. The sensitivity, specificity, positive predictive value, negative predictive value, accuracy, and likelihood ratio were calculated using a 2x2 TABLE. Youden’s index was used to choose the proper cutoff level of CHr for diagnosing iron deficiency. The study was conducted on 104 subjects. Cutoff level of CHr was ≤27.65 pg and the sensitivity, specificity, diagnostic accuracy, positive, and negative predictive values were 91.7%,78.3%, 79.8%, 35.4%, 98.63% respectively. Positive and negative results of likelihood ratios were 4.21 and 0.1. CHr is expected to be used to screen iron deficiencyin children under 5 years old.